2022
DOI: 10.1007/s12350-020-02396-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of incidental suspected transthyretin amyloidosis on routine bone scintigraphy

Abstract: Background Transthyretin amyloidosis (ATTR) is an occasional incidental finding on bone scintigraphy. We studied its prognostic impact in elderly patients. Methods The study population consisted of 2000 patients aged over 70 years who underwent bone scintigraphies with clinical indications in three nuclear medicine departments (Kymenlaakso, Jorvi and Meilahti hospitals) in Finland. All studies were performed using 99mTechnetium labeled hydroxymethylene diphosphonate (HMDP). ATTR was suspected in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…Per current guidelines, H/CL ≥ 1.5 is positive, < 1.0 is negative, and in between is equivocal ( 75 ). Some physicians use a cutoff of H/CL ≥ 1.3 to increase sensitivity ( 80 ). Other signal ratios are scattered throughout the literature including heart to whole body (H/WBR) and heart to skull (H/S).…”
Section: Nuclear Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Per current guidelines, H/CL ≥ 1.5 is positive, < 1.0 is negative, and in between is equivocal ( 75 ). Some physicians use a cutoff of H/CL ≥ 1.3 to increase sensitivity ( 80 ). Other signal ratios are scattered throughout the literature including heart to whole body (H/WBR) and heart to skull (H/S).…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…These characteristics also correlate with degree of amyloid deposition on CMR ( 58 ). The initial use in more advanced disease led to high sensitivity and specificity but more contemporary ordering practices aimed at early diagnosis may have less uptake which may not be detectable below a certain amount of total amyloid deposition ( 74 , 80 82 ). However, the lower sensitivity is not entirely explained by early disease as some patients with advanced disease by symptoms and other imaging have grade 0/1 uptake ( 83 , 84 ).…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…effects. 7 Aside from solid organ transplantation, the only effective treatment that is currently FDA-approved, the transthyretin stabilizer tafamadis, works by preventing further accumulation of the misfolded protein in cardiac tissues. While this treatment offers a remarkable survival benefit, this benefit was only seen starting approximately 18 months after initiation of therapy.…”
mentioning
confidence: 99%
“…Given its many positive attributes, it has been suggested that cardiac scintigraphy could represent a new non-invasive ''gold standard'' for diagnosis, although both pre-test probability of ATTR-CA in a population as well as reader/ technician experience remain important considerations in the utility of this test. 16 Given the importance of early diagnosis of ATTR-CA and the potential of cardiac scintigraphy to identify subclinical disease, in this issue of the Journal of Nuclear Cardiology Suomalainen et al 7 explored whether there was prognostic significance to incidentally found suspected ATTR-CA on bone scintigraphy studies performed for other reasons. This study evaluated 2000 patients over the age of 70 and compared the risk of overall and cardiovascular mortality between patients with positive 99m Tc-HMDP scans (grade 2 uptake or H/ CL ratio [ 1.30 at 3 hours) and those with negative ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation